Esophagus traumatisms
Their frequency is discussed. polnting out lhe gr cnt prepondel'ance of endoscopic and foreign-body injuries. Clinicol diagnosis is rather simple in thc períoratlor1! ol cervical c.sophagus, but not so simple in the perforations of thoraclc esophagUIi. Antecedents ond roentg nography are cssential for the diagnosis. Thc Irt>atment 01 cervical perCorations has been long d.iscus sed. hut th author is prone 10 perform suraiea